A Case Report of Male infertility and Gynecomastia in High Altitude Area: Clinical Evaluation and Management - Syed Intesar Burni, Sameera Ali Rizvi, Fareena Khalil, Mehwish Asad, Tazeen Saeed Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Gynecomastia is a common abnormality of breast tissue among men. It is the benign enlargement of male breast glandular tissue. In this report a narrative approach was followed for the qualitative inquiry of three men from the high altitude areas of Pakistan. They presented with gynecomastia and infertility. These men were approached for clinical examination, lab investigations, and further management. The semen findings of these patients showed oligospermia, azoospermia or necrospermia. Serum Prolactin was found to be high and they were overweight with increased breast development. The Serum Prolactin, FSH, LH levels, and Testosterone levels were measured in these patients with infertility. The laboratory investigations of our patients showed high prolactin and estrogen levels. All these men were reported stress due to erectile dysfunction and infertility. The reasons of male infertility in the high-altitude areas of Pakistan need to be explored further.